2018
DOI: 10.1080/14767058.2018.1424822
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and outcomes of antenatal tests for infections: a population based survey in the Province of Trento, Italy

Abstract: Our study indicates that the attention to screening and detecting infected cases is growing over the time. In addition, care delivered during pregnancy has a leading role in determining coverage of the examinations. Immigrant, pluriparous and less educated women need particular attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…Prevalence in pregnant women is also consistent with this trend toward a decrease observed in Italy. Epidemiological studies conducted on T. gondii seroprevalence in pregnant women between the 1980's and 1990's revealed rates ranging from 40.4% in Naples to 48.7% in the area of Parma [3,4,30], whereas more recent studies have found rates of T. gondii prevalence in pregnant women between 21.5% and 27.5% [5,7,8,26]. Pregnant women in this study showed a further decrease, with an overall prevalence of 13.8%.…”
Section: Discussioncontrasting
confidence: 52%
“…Prevalence in pregnant women is also consistent with this trend toward a decrease observed in Italy. Epidemiological studies conducted on T. gondii seroprevalence in pregnant women between the 1980's and 1990's revealed rates ranging from 40.4% in Naples to 48.7% in the area of Parma [3,4,30], whereas more recent studies have found rates of T. gondii prevalence in pregnant women between 21.5% and 27.5% [5,7,8,26]. Pregnant women in this study showed a further decrease, with an overall prevalence of 13.8%.…”
Section: Discussioncontrasting
confidence: 52%
“…Given the sensitivity of the data, access to the SIO must also take place in a manner aimed at ensuring the maximum possible confidentiality. The coverage of the GBS testing is, in the period under study, always greater than 90%, a value consistent with what was reported in our previous overall study and, as regards specifically the GBS, higher than that reported by a previous national survey by the National Institute of Health and other regional studies [3,5,24,25]. Coverage of GBS testing is higher in term births and in spoke maternity units, as reported by a previous Italian work [5].…”
Section: N Discussionsupporting
confidence: 90%
“…This allows an assessment by area rather than by centers, similarly to what has already been reported, for the Italian level, in the Emilia-Romagna region. An overall report on the surveillance of infections in pregnancy through the BAC in the province of Trento, for the period 2007-2014, was provided by our previous study [24]. However, this study represents our first in-depth evaluation of GBS infection in pregnancy.…”
Section: N Discussionmentioning
confidence: 99%
“…Consistent with the two studies mentioned above, several authors claim that there is a decreasing trend in T. gondii infection among pregnant women (38). Epidemiological studies conducted on T. gondii seroprevalence in pregnant women before the 2000's revealed rates ranging from 40.4% to 48.7% in two areas of Italy, whereas some recent studies have found rates of T. gondii prevalence in pregnant women between 21.5 and 27.5% (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 55%